Becoming agile : (Jossey-Bass, 2015)
Becoming Agile: How the SEAM Approach to Management BuildsAdaptability illustrates the process of becoming an agileorganization. Reflecting the principles presented in The AgilityFactor, readers are taken on a real-world journey oftransformation and change. This short-format case study of theFrench company Brioche Pasquier highlights how one organizationsuccessfully implemented the principles of agility using thesocio-economic approach to management, detailing each step of theprocess and describing how every decision brought the goal closerwithin reach. Readers get inside the heads of decision makers togain insight into how tough decisions were made, how new,important, and flexible management tools were implemented, and howthe necessary changes ultimately benefitted both the organizationand the people who made it work. From overarching policy today-to-day procedure, the story provides a clear example of how anagile organization is developed, giving readers a foundation uponwhich to implement similar changes in their own organization.